Concussion knowledge and experience among a sample of American adults. (April 2018) - Waltzman, Dana; Daugherty, Jill
Background: Recently, there has been a strong emphasis on educating athletes, parents, coaches, and health care providers about concussions. However, not much is known about whether these efforts are affecting the general public's level of concussion knowledge. Purpose: To determine what is currently known among the public about concussions and where education campaigns may be targeted in order to fill in the gaps. Methods: In order to achieve the project's objective, CDC analyzed self-reported data from Porter Novelli's 2017 SummerStyles survey, an annual survey of American adults aged 18 and older across the United States. The questions focused on personal concussion experiences, basic concussion knowledge, knowledge of prevention strategies, and perceived best sources of information about concussion. Results: Analysis of the data showed that approximately 18% of respondents reported that they had personally experienced a concussion in their lifetime, and about two-thirds of these respondents were evaluated by a health care provider after their injury. In terms of concussion knowledge, the majority were aware of common causes of concussion. While 94% knew that headache was a symptom of concussion, just over half were aware that sleep problems were as well. Most respondents (>78%) correctly identified that wearing seat-belts, preventing falls, and reducing participation in contact sports were ways to prevent a concussion, while installing baby-gates across stairs was less frequently known (65.5%) as a prevention technique. Nearly all of the respondents believed that a doctor or other health professional was a good source of information about concussions. These results varied by age, sex, race/ethnicity, and education. Conclusion: The results demonstrate that even though the public has a relatively high knowledge level of concussion, targeted education is needed to teach American adults about the symptoms and ways of getting a concussion.